Students' Satisfaction with Life and Its Relation to School Burnout - Vali Mehdinezhad (University of Sofia, 2015)
The purpose of this study was to investigate the relationship between school burnout and satisfaction with life for students in grade of 7th to 9th. A quantitative method used in this study. 351 subjects were selected using stratified sampling. The two questionnaires employed here were The Satisfaction with Life Scale with five items of the Diener et al. (1985) and School-Burnout Inventory with nine items and three component - exhaustion at schoolwork (EXH), cynicism toward the meaning of school (CYN), and sense of inadequacy at School (INAD) - measures of school burnout of the Salmela-Aro et al. (2009). The findings of this study showed that the high school students described their satisfaction with life in relatively satisfactory and they have described their level of school burnout lower than average. The results also showed their school burnout in component of exhaustion at schoolwork was above average and in Components of cynicism toward the meaning of school, and sense of inadequacy at School were lower than average. The results showed that in overall there was no significant correlation between satisfaction with life and school burnout. However, there was relatively low positive correlation between students' satisfaction with life and exhaustion at schoolwork, relatively low negative correlation between students' satisfaction with life and cynicism toward the meaning of school, and no any significance correlation between students' satisfaction with life and sense of inadequacy at school. The results of stepwise regression showed that sub-dimensions of high school burnout scale together explained a total of 14.5 % of the variance in the satisfaction with life for the students in this study.